Normal-Weight Obesity Is Associated with Increased Cardiometabolic Risk in Young Adults - Correa-Rodríguez, María; González-Ruíz, Katherine; Rincón-Pabón, David; Izquierdo, Mikel; García-Hermoso, Antonio; Agostinis-Sobrinho, Cesar; Sánchez-Capacho, Nohora; Roa-Cubaque, Marcela América; Ramírez-Vélez, Robinson (Nutrients, 2020)
Normal-weight obesity (NWO) has been shown to be associated with cardiometabolic dysfunction. However, little is known regarding this potential relationship in early adulthood. The aim of this study was to investigate the associations between NWO and cardiometabolic risk factors in a large population of Colombian young adults. A cross-sectional study was conducted on 1354 subjects (61% women), aged from 18 to 30. Anthropometric data, including body mass index (BMI) and waist circumference (WC), were estimated, and the percentage of fat mass was measured through bioelectrical impedance analysis (BIA). Muscular fitness was determined by using a handgrip strength test and normalized grip strength (NGS = handgrip (kg)/body mass (kg)). A cardiometabolic risk Z-score was derived by assessing WC, triglycerides, high-density lipoprotein cholesterol (HDL-C) cholesterol, fasting glucose, and systolic blood pressure. NWO was defined by the combination of excess %BF (over 25.5% for men and 38.9% for women) and a BMI < 25 kg/m2. The overall prevalence of NWO was 29.1%. Subjects with NWO have an increased risk of cardiometabolic risk compared to the normal-weight lean group (OR = 3.10). Moreover, NWO was associated with an increased risk of presenting low HDL-C (OR = 2.34), high abdominal obesity (OR = 7.27), and low NGS (OR = 3.30), p < 0.001. There is a high prevalence of NWO in American Latin young adults and this condition is associated with an increased cardiovascular risk, high blood pressure, low HDL-C, high abdominal obesity, and low muscular strength early in life. Screening for adiposity in subjects with a normal BMI could help to identify young adults at a high risk of cardiometabolic abnormalities.